EXTRA-CURRICULAR EDUCATIONAL WORK AT CHUVASH STATE UNIVERSITY - O. N. Viktorov (Высшее образование в России)
Extra-curricular educational work plays an important role in the formation of professional competences and civic, general cultural qualities of students. The article presents the experience of organization and management of extra-curricular educational work at Ulianov Chuvash State University. The author dwells on the activity of the curators' school and the projects and programs realized at the University in the areas ofthe spiritual, moral and patriotic education of students.